3PC-005 A new packaging of hypertonic solution to overcome an unavailable formulation in france. (2nd March 2018) - Gicquel, C; Vandewoestyne, S; Semely, D; Ramjaun, Z; Tafani, M
Abstract : Background: Mannitol is considered the gold standard hyperosmolar agent to decrease intracranial pressure (ICP) after traumatic brain injury. However, solutions of mannitol may crystallise when exposed to low temperatures, for example at high altitude or during helicopter rescues. If crystals are observed, the container should be warmed, shaken and then cooled to body temperature before administration which is inappropriate in daily emergency practice. Several studies show that hypertonic saline solution (HTSS) is comparable or potentially superior to mannitol: furthermore HTSS might have less adverse effect than mannitol and does not crystallise with low temperature. HTSS only exists in 500 mL glass vials, unfit for emergency practices which need compact unbreakable packaging. Purpose: To provide for emergency practices a ready-to-use HTSS of 7.5% sodium chloride infusion bag. Material and methods: Infusion bags were produced by aseptic process using the BAXA ® EM2400 compounder. Ingredients used were sterile sodium chloride 20% (AGEPS ® ) and water for injectable preparation (Bbraun ® ) filled in an ethyl vinyl acetate infusion bag of 100 ml. Bags were stored at room temperature without light protection. Microbiological stability was assessed by performing sterility and endotoxin tests. The physicochemical study was performed by determining visual aspect, osmolality, sodium and chloride concentration at 0, 30 and 90 days. Results: Neither precipitate nor any change in colour was observed after 90 days. Ion concentrations remained unchanged with 1320 mM (+3%); 1290 mM (+1%); 1240 mM (−3%) and osmolality of the HTSS were found to be 2560 mosm/L (0%); 2420 (-6%); and 2350 mosm/L (9%) respectively at 0, 30 and 90 days. At each time point, all microbiological results were negative. Conclusion: The automated compounding ensures quality and safety of production for a ready-to-use HTSS of 7.5% sodium chloride with a best-before-date of 90 days. The stability study is still on-going. Reference and/or Acknowledgements: 1. Helmy A, Vizcaychipi M, Gupta AK: Traumatic brain injury: intensive care management. Br J Anaesth, 2007; 99: 32–42. No conflict of interest